Patient perspectives of vigorous intensity aerobic interval exercise prehabilitation prior to radical cystectomy: a qualitative focus group study. Issue 8 (10th April 2021) - Banerjee, Srijit; Semper, Kelly; Skarparis, Katy; Naisby, Jenni; Lewis, Liane; Cucato, Gabriel; Mills, Robert; Rochester, Mark; Saxton, John
Abstract: Purpose: Preoperative cardiopulmonary fitness is increasingly being recognized as an important factor influencing postoperative recovery outcomes in cancer patients. The aim of this study was to explore patient perspectives of preoperative high intensity aerobic interval exercise before radical cystectomy. Materials and methods: Focus groups involving a purposive convenience sample of patients with bladder cancer ( N = 14; mean age ± SD: 72.3 ± 6.0 years) were undertaken in a hospital education department. Data were analyzed using Framework analysis. Results: Participants identified physical (e.g., fitness) psychological (e.g., preparing for their operation) and social (e.g., peer support) benefits of the program. Key motivational factors for engaging in exercise prehabiliation were identified as social support, previous exercise experience and objective measures of progression. The need for clear information from healthcare providers to ensure that patients are adequately prepared for sessions was highlighted. Conclusions: This qualitative study provides new insights into the perspectives and experiences of patients with bladder cancer regarding participation in preoperative vigorous intensity aerobic exercise. The study yielded novel perceptions on the physical, psychological and social health benefits accruing from the exercise program and patient views on program design features, which are important for informing future interventions and implementation strategies. IMPLICATIONS FOR REHABILITATION: A preoperative high intensity aerobic interval exercise program before radical cystectomy provides physical, psychological and social benefits to individuals living with bladder cancer. Supervised exercise, objective improvement, and peer and family support all contribute to motivation to engage with preoperative high intensity aerobic interval exercise. Individuals may require support post-radical cystectomy in order to continue with exercise due to the uncertainty around this.